Official Social Security Administration answers to 100 frequently asked questions about retirement (Welcome Rain Publishers, 2018)
"For most Americans, Social Security is their largest financial asset, worth hundreds of thousands of dollars and indexed against increases in the cost of living. It is also an incredibly complicated program, with 2,728 core rules and thousands of codicils. As a result, Americans lose billions of dollars a year in unclaimed benefits. This money that we have earned and are entitled to, that is lost forever. If you are thinking about retirement, you'll want to know how much you can expect to get from Social Security, and what you can do to maximize your benefit. The information contained in this book is "Official" because it comes directly from the Social Security website and publications. The editor has sifted through many thousands of pages of SSA publications to find the answers to the most important questions you may have, and organizes and presents them here in a useful and coherent manner. THIS BOOK IS NOT published, authorized, or endorsed by the Social Security Administration."--Page [4] of cover.